An Intrinsically Stretchable and Compressible Supercapacitor Containing a Polyacrylamide Hydrogel Electrolyte - Huang, Yan; Zhong, Ming; Shi, Fukuan; Liu, Xiaoying; Tang, Zijie; Wang, Yukun; Huang, Yang; Hou, Haoqing; Xie, Xuming; Zhi, Chunyi (Angewandte Chemie International Edition, 2017)
Stretchability and compressibility of supercapacitors is an essential element of modern electronics, such as flexible, wearable devices. Widely used polyvinyl alcohol‐based electrolytes are neither very stretchable nor compressible, which fundamentally limits the realization of supercapacitors with high stretchability and compressibility. A new electrolyte that is intrinsically super‐stretchable and compressible is presented. Vinyl hybrid silica nanoparticle cross‐linkers were introduced into polyacrylamide hydrogel backbones to promote dynamic cross‐linking of the polymer networks. These cross‐linkers serve as stress buffers to dissipate energy when strain is applied, providing a solution to the intrinsically low stretchability and compressibility shortcomings of conventional supercapacitors. The newly developed supercapacitor and electrolyte can be stretched up to an unprecedented 1000 % strain with enhanced performance, and compressed to 50 % strain with good retention of the initial performance. S‐T‐R‐E‐T‐C‐H: An easily fabricated polyacrylamide hydrogel electrolyte incorporated into a supercapacitor instills the device with intrinsic and unprecedented super‐stretchability (1000 % strain with enhanced performance) and high compressibility (50 % strain with retained capacitance).